Confinement Aided Simultanous Water Cleaning and Energy Harvesting Using Atomically Thin Wurtzite (Wurtzene). (16th December 2020) - Kumbhakar, Partha; Mukherjee, Madhubanti; Pramanik, Ashim; Karmakar, Srikanta; Singh, Abhishek K.; Tiwary, Chandra S.; Kumbhakar, Pathik
Abstract: Syntheses of few‐layered piezocatalysts from nonlayered materials have gained a huge attention of attention in recent years due to their potential applicability in efficient removal of toxic elements from water. Here, a simple scalable bottom up approach consisting of wet‐chemical synthesis method is used to produce the atomically thin (2D)‐wurtzite ZnO: "wurtzene." The presence of a large number of well‐distributed surface defects in the synthesized wurtzene promotes the separation of charge carriers in it via the excellent piezo‐photocatalytic activity and thereby the efficiency of degradation of a test dye (namely methylene blue) is enhanced by ≈5 times. By taking an innovative approach, a piezoelectric driven power cell is also fabricated by using the wurtzene and the highest open circuit voltage is found out to be ≈40 V at 1.0 kPa of applied periodic pressure. The experimental observations are explained with density functional theory calculation. The confinement effect due to reduced dimension plays a crucial role in the wurtzene's excellent piezoelectric response. It is envisioned that the present findings will provided a clear insight into the synthesis of wurtzene with surface defects for highly efficient sunlight driven photocatalytic activity as well as piezoelectric energy harvesting. Abstract : Atomically thin wurtzite ZnO, named as "Wurtzene" is synthesized. An enhancement in dye degradation efficiency by a factor of five is achieved by the piezo‐photocatalytic process in comparison to that by photocatalysis. Additionally, the mechanism of generation of piezo voltage from the fabricated device is explained using density functional theory.